PH response type anti-adhesion antibacterial nanorod coating based on bacteriophage endolysin - LI HEXUE; SHI HUI (2025)
The invention discloses a pH response type nanorod intelligent antibacterial coating constructed on the surface of stainless steel for the first time. According to the coating, stimuli-responsive polymer polyacrylic acid (PAA) and phage-derived endolysin Lys81 are grafted to a ZnO nano-column, and self-regulation is carried out in response to environmental conditions. In the initial stage of bacterial adhesion, the surface of the nanorod shows remarkable mechanical bactericidal activity, and the bacterial adhesion is effectively inhibited by the super-hydrophilic PAA layer. In a later stage, when many live bacteria and dead bacteria adhere to the surface of the nanorod, the PAA chain disintegrates, exposing the endolysin bottom layer that lyses the damaged bacteria. In addition, along with the increase of the pH value of the environment, the attached dead bacteria can be released once the hydrophilicity of the PAA chain is recovered. The purpose of the present invention is to apply an antibacterial coating to